Annual Plant Reviews Online 2017
DOI: 10.1002/9781119312994.apr0486
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analyses and Morphological Innovations in Land Plants

Abstract: An increasingly robust phylogenetic framework based on molecular and fossil data clarifies the sequence of evolutionary innovations in land plants. Oogamy and cellular novelties (phragmoplast, plasmodesmata, incipient meristems) evolved in aquatic streptophytes. Invasion of the land entailed interpolation of the sporophyte, jacketed gametangia and sporangia, and air‐dispersed spores, followed by stomata. Origin of vascular plants involved branching of the sporophyte and stepwise evolution of vascular tissue. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 226 publications
2
39
0
3
Order By: Relevance
“…Although initial characterization in a heterologous system suggested that PINA was ER localized and PIND cytosolic [7], analysis of these proteins in their native context demonstrates that, consistent with their structures, PINA is plasma membrane localized and PIND is ER localized [27,28]. PINA sometimes shows polar localization, but can be also apolarly localized depending on tissue and developmental stage [28] The plant phylogeny presented here is based on current consensus, and follows that presented in [18]. It should be noted that the phylogeny is not definitive, and some details remain unresolved or controversial; for instance, there is currently uncertainty regarding the relative positions of Charales and Zygnematales (as illustrated here), and regarding the interrelation of the bryophyte groups.…”
Section: Trends In Plant Sciencementioning
confidence: 73%
See 4 more Smart Citations
“…Although initial characterization in a heterologous system suggested that PINA was ER localized and PIND cytosolic [7], analysis of these proteins in their native context demonstrates that, consistent with their structures, PINA is plasma membrane localized and PIND is ER localized [27,28]. PINA sometimes shows polar localization, but can be also apolarly localized depending on tissue and developmental stage [28] The plant phylogeny presented here is based on current consensus, and follows that presented in [18]. It should be noted that the phylogeny is not definitive, and some details remain unresolved or controversial; for instance, there is currently uncertainty regarding the relative positions of Charales and Zygnematales (as illustrated here), and regarding the interrelation of the bryophyte groups.…”
Section: Trends In Plant Sciencementioning
confidence: 73%
“…In this case, PAT could also be a shared-ancestral characteristic of charophytes and land plants, and PIN proteins in the Charales might be rather more similar to canonical PINs than to KfPIN and/or SpPIN ( Figure 1). An alternative view is that the simple algae in the Zygnematales are the sister group to embryophytes [19,20], which would have required them to undergo severe reductions in complexity [18,20]. If Zygnematales are sister to embryophytes, then either most of the canonical PIN structure evolved after their divergence, or SpPIN has also undergone reduction from ancestral proteins that were more canonical in structure (and it is notable that SpPIN is less similar to canonical PINs than is KfPIN).…”
Section: Auxin Transport and Pins In Algaementioning
confidence: 95%
See 3 more Smart Citations